A Review of the MFS Regulatory Framework to Control IFF in Bangladesh - Huda, MD. Nazmul; Sony, M M Abdullah Al Mamun (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Mobile financial services (MFS), with their focus on technology and ease of use, have emerged as a novel approach for developing countries to address the problem of adopting best practices to promote financial inclusivity. However, if there are no effective regulations or guidelines in place on a national and international level, the purpose of achieving full financial inclusion and the Sustainable Development Goals might go in vain. For instance, to prevent illicit financial flow (IFF) and ensure that this financial system operates properly, the central bank of Bangladesh, one of the world’s fastest-developing nations, implemented the most recent MFS rule. However, a number of MFS-related fraud incidents have prompted scholars to critically assess the Bangladesh Bank’s (BB) MFS regulatory system with a focus on the efficiency of IFF prevention. This study has demonstrated that the current regulatory system has a weak KYC verification system using a comparative methodology. Following that, if someone has access to someone’s personal information, they also have access to their MFS accounts. In general, the current MFS adheres to a risk-based regulatory paradigm that forces regulators to wait until a hazard occurs and limits them to this legal framework. Policy makers would then be advised by this study to implement a smart regulatory approach in order to establish a climate that is anti-IFF.